Psychometric development of a moral distress scale for healthcare education and practice - Liao, Hung-Chang; Wang, Ya-Huei (Frontiers in Psychology, 2025)
ObjectiveUnaddressed moral distress may result in psychological, emotional, and physical consequences. The study was to develop and validate a Moral Distress Scale for Healthcare Students and Providers (MDS-HSP) within the Taiwanese healthcare education and clinical contexts, providing a framework for administrators and policymakers to recognize and respond to moral distress in training and practice settings.MethodsFollowing an extensive literature review and expert discussions, the study performed an exploratory factor analysis (EFA) using SPSS with a sample of 332 participants to determine the hidden structure of the MDS-HSP and evaluate its initial psychometric properties. A subsequent confirmatory factor analysis (CFA) using AMOS with a separate sample of 240 participants was performed to verify the identified factor structure. The testing process included the assessments of validity, reliability, and goodness-of-fit analysis.ResultsFollowing the EFA, the initial 72 items were refined to 42 items across six factors: “acquiescence to patients’ rights violations” (8 items), “lack of professional competence” (9 items), “disrespect for patients’ autonomy” (10 items), “futile treatment” (5 items), “organizational and social climate” (6 items), and “not in patients’ best interest” (4 items). The CFA confirmed the same six scale factors and 42 items. Both EFA and CFA supported the proposed factor structure and demonstrated adequate validity and reliability.ConclusionThe study provided empirical evidence supporting the MDS-HSP as a reliable tool for assessing moral distress experienced by healthcare students and providers. Its use may inform educational strategies, institutional policies, and ethical support mechanisms within healthcare and academic settings.